Synthesis of carbon nanofibers on impregnated powdered activated carbon as cheap substrate - Al-Mamun, Abdullah; Ahmed, Yahya; Muyibi, Suleyman Aremu; Al-Khatib, Ma'an Fahmi Rashid; Jameel, Ahmed TariQ; AlSaadi, Mohammed A. (ELSEVIER SCIENCE BV, 2016)
The catalysis and characterization of carbon nanofibers (CNFs) composite are reported in this work. Carbon nanofibers were produced on oil palm shell powdered activated carbon (PAC), which was impregnated with nickel. Chemical Vapor Deposition (CVD) of C2H2 was used in the presence of hydrogen at ~ 650º C. The flow rates of carbon source and hydrogen were fixed. The CNFs were formed directly on the surface of the impregnated PAC. Variable weight percentage (1, 3, 5, 7 and 9%) of the catalyst salt (Ni+2) were used for the impregnation. However, the best catalysis was observed on the substrate with 3% Ni2+. The product displayed a relatively high surface area, essentially constituted by the external surface. New functional groups were also appeared compared to those in the PAC. Field Emission Scanning Microscopy (FESEM), Transmission Electron Microscopy (TEM), Fourier Transform Infrared (FTIR), BET surface area analysis and Energy Dispersive X-ray analyzer (EDX) were used for the characterization of the new carbon nano product, which was produced through a clean novel process.